Multidisciplinary Approaches in General Medical Practice: Enhancing Collaboration for Better Patient Care - Alsubaie, Saad Saud; Bukhamseen, Zainab Fadhle Abbas; Alyami, Faisal Saeed Ahmed; Alotaibi, Majed Faris; Alkahtani, Fawaz Abdullah; Alkhamsan, Mohammed Saeed; Alaseel, Ahmed Jaffer; Albahri, Mansour Awadh Saeed; Bahrani, Janan Ibrahim Ali Al; Khamees, Zainab Habib Al (Journal of Ecohumanism, 2024)
Multidisciplinary approaches in general medical practice have become integral to providing comprehensive, patient-centered care, as the complexity of modern health issues often requires a diverse range of expertise. This review explores the role and benefits of multidisciplinary teams in enhancing patient outcomes, improving resource efficiency, and increasing patient satisfaction in general medical settings. By examining the contributions of various healthcare professionals—including primary care physicians, specialists, allied health professionals, and behavioral health specialists—this review emphasizes how collaborative efforts address complex health needs more effectively than traditional, siloed approaches. Key case studies illustrate successful multidisciplinary practices in managing chronic diseases and complex conditions, highlighting the advantages of coordinated care models. The review also addresses challenges, such as communication barriers, hierarchical dynamics, and logistical constraints, that can hinder effective collaboration. Furthermore, it discusses technological supports, such as electronic health records (EHR) and telemedicine, which facilitate real-time communication and care coordination. The article concludes with recommendations for expanding multidisciplinary teams in primary care, promoting educational initiatives for team-based care skills, and advocating for policy support to institutionalize multidisciplinary approaches in general medicine. These findings suggest that well-coordinated multidisciplinary teams can transform patient care, making it more holistic, efficient, and responsive to individual needs.